Single- vs. Double-Bundle Anterior Cruciate Ligament Reconstruction: A New Aspect of Knee Assessment During Activities Involving Dynamic Knee Rotation. Issue 2 (February 2015) - Czamara, Andrzej; Królikowska, Aleksandra; Szuba, Łukasz; Widuchowski, Wojciech; Kentel, Maciej
Abstract : Abstract: Czamara, A, Królikowska, A, Szuba, L, Widuchowski, W, and Kentel, M. Single- vs. double-bundle anterior cruciate ligament reconstruction: A new aspect of knee assessment during activities involving dynamic knee rotation. J Strength Cond Res 29(2): 489–499, 2015—Few studies have compared single-bundle (SB) and double-bundle (DB) anterior cruciate ligament reconstruction (ACLR) in the knee joint during activities involving change-of-direction maneuvers and knee rotation. This study examined whether the type of ACLR contributes to postphysiotherapy outcomes, with an emphasis on knee function assessment during activities involving dynamic knee rotation. Fifteen male patients after SB ACLR and 15 male patients after DB ACLR took part in the same physiotherapy program. Twenty-four weeks after ACLR, both groups underwent anterior laxity measurement, pivot shift tests, range of movement and joint circumference measurements, subjective assessment of pain and stability levels in the knee joint, peak torque measurement of the muscles rotating the tibia toward the femur, and a run test with maximal speed and change-of-direction maneuvers. Comparative analysis did not show any differences between the results of anterior tibial translation, pivot shift test, range of movement and joint circumference, and subjective assessment of pain and knee joint stability levels. No differences were noted between the groups in peak torque values obtained from the muscles responsible for internal and external tibial rotation or results of the run test. The data obtained from this study can be used by research teams to monitor and compare the effectiveness of various study protocols involving surgical and physiotherapy treatment. The data are especially useful when combined with the clinical assessment of patients who would like to return to sport.